Longitudinal Antibody Dynamics Against Structural Proteins of SARS-CoV-2 in Three COVID-19 Patients Shows Concurrent Development of IgA, IgM, and IgG - Jamiruddin MR (Dove Medical Press, 2021)
Mohd Raeed Jamiruddin,1 Md Ahsanul Haq,2 Kazuhito Tomizawa,3 Eiry Kobatake,4 Masayasu Mie,4 Sohel Ahmed,5 Shahad Saif Khandker,2 Tamanna Ali,2 Nowshin Jahan,2 Mumtarin Jannat Oishee,2 Mohib Ullah Khondoker,2 Bijon Kumar Sil,2 Mainul Haque,6 Nihad Adnan7 1Department of Pharmacy, BRAC University, Dhaka, 1212, Bangladesh; 2Gonoshasthaya-RNA Molecular Diagnostic & Research Center, Dhaka, 1205, Bangladesh; 3Department of Molecular Physiology, Graduate School of Medical Sciences, Kumamoto University, Kumamoto, 860-0811, Japan; 4School of Life Science and Technology, Tokyo Institute of Technology, Yokohama, Kanagawa, 226-8502, Japan; 5Department of Biochemistry and Molecular Biology, Jahangirnagar University, Savar, Dhaka, 1342, Bangladesh; 6The Unit of Pharmacology, Faculty of Medicine and Defence Health, Universiti Pertahanan Nasional Malaysia (National Defence University of Malaysia), Kuala Lumpur, 57000, Malaysia; 7Department of Microbiology, Jahangirnagar University, Savar, Dhaka, 1342, BangladeshCorrespondence: Nihad AdnanDepartment of Microbiology, Jahangirnagar University, Savar, Dhaka, 1342, BangladeshTel +8801705709910Email nihad@juniv.eduMainul HaqueThe Unit of Pharmacology, Faculty of Medicine and Defence Health, Universiti Pertahanan Nasional Malaysia (National Defence University of Malaysia), Kem Perdana Sungai Besi, Kuala Lumpur, 57000, MalaysiaTel +60109265543Email runurono@gmail.comBackground: Dynamics and persistence of neutralizing and non-neutralizing antibodies can give us the knowledge required for serodiagnosis, disease management, and successful vaccine design and development. The disappearance of antibodies, absence of humoral immunity activation, and sporadic reinfection cases emphasize the importance of longitudinal antibody dynamics against variable structural antigens.Methods: In this study, twenty-five healthy subjects working in a SARS-COV-2 serodiagnostic assay development project were enrolled, and their sign and symptoms were followed up to six months. Three subjects showed COVID-19-like symptoms, and three subjects’ antibody dynamics were followed over 120 days by analyzing 516 samples. We have developed 12 different types of in-house ELISAs to observe the kinetics of IgG, IgM, and IgA against four SARS-CoV-2 proteins, namely nucleocapsid, RBD, S1, and whole spike (S1+S2). For the development of these assays, 30– 104 pre-pandemic samples were taken as negative controls and 83 RT-qPCR positive samples as positive ones.Results: All three subjects presented COVID-19-like symptoms twice, with mild symptoms in the first episode were severe in the second, and RT-qPCR confirmed the latter. The initial episode did not culminate with any significant antibody development, while a multifold increase in IgG antibodies characterized the second episode. Interestingly, IgG antibody development concurrent with IgM and IgA and persisted, whereas the latter two weans off rather quickly if appeared.Conclusion: Antibody kinetics observed in this study can provide a pathway to the successful development of sero-diagnostics and epidemiologists to predict the fate of vaccination currently in place.Keywords: antibody dynamics, COVID-19, SARS-CoV-2, reinfection, vaccination